Variabel-variabel yang Memengaruhi Ketuntasan Wajib Belajar di Provinsi Papua Tahun 2020 - Nurul Aulia Rahmi; Liza Kurnia Sari (Seminar Nasional Official Statistics, 2022)
In Indonesia, there are still several provinces with low educational attainment, one of which is Papua Province. It is known that the rate of continuing to high school/equivalent in Papua is still below the national figure. In addition, the average length of schooling in Papua Province ranks last in Indonesia. This study aims to analyze the variables that affect the 12-year compulsory education completeness in Papua Province in 2020 using Susenas March 2020 data. The research method uses binary logistic regression analysis. The results showed that 43.6 percent of the population aged 18-24 years in Papua Province had completed 12 years of compulsory education. Compulsory education completeness is more likely to occur in people aged 18-24 years who live in urban areas, have male household heads, have household heads with high school education/equivalent, reside in households with less than or equal to 4 household members, have KIP and reside in a household with per capita expenditure above the poverty line.